Влияние корма на некоторые гематологические показатели и газообмен серой полевки (Microtus arvalis Pall.) - Шевченко, Н.Т. (Вестник зоологии, 1969)
The influence of fodder on the oxygen consumption, hemoglobin content and quantity
of erythrocytes in the blood of Microtus arvalis Pall, was studied. A considerable
influence of different fodder on the hemoglobin content was marked. The influence of fod-
der on the erythrocyte quantity and oxygen consumption is considerably less in these
two indices. Considerable individual variability is observed